2018
DOI: 10.18203/2320-1770.ijrcog20180857
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia gene mutations in relation to recurrent miscarriage

Abstract: Background: Recurrent pregnancy loss is multifactorial involving clinical and biological risk factors. Evidence addressed the association of inherited thrombophilia with recurrent pregnancy loss and other serious pregnancy complications. However, the relation between thrombophilia associated gene mutations and adverse obstetric outcome is controversial and data in the literature are inconsistent. The aim of this study was to investigate the prevalence of thrombophilia associated gene mutations (factor V Leiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Other large prospective studies reported contradictory results stating that hypercoagulable thrombophilic gene mutations are not increased in women with recurrent miscarriage [16], [17]. In another study conducted by Henry et.al, [18], they confirmed the low prevalence of inherited thrombophilias in non-Caucasian populations and it is unlikely that the tested thrombophilias play a role in the pathogenesis of recurrent pregnancy loss in this Colombian population. They are also congruent with another study conducted by Abu-Asab et al, they did not find a significant association between FVL, FII, and MTHFR and RPL in the first and second trimester [19].…”
Section: Discussionmentioning
confidence: 82%
“…Other large prospective studies reported contradictory results stating that hypercoagulable thrombophilic gene mutations are not increased in women with recurrent miscarriage [16], [17]. In another study conducted by Henry et.al, [18], they confirmed the low prevalence of inherited thrombophilias in non-Caucasian populations and it is unlikely that the tested thrombophilias play a role in the pathogenesis of recurrent pregnancy loss in this Colombian population. They are also congruent with another study conducted by Abu-Asab et al, they did not find a significant association between FVL, FII, and MTHFR and RPL in the first and second trimester [19].…”
Section: Discussionmentioning
confidence: 82%
“…This inherited deficiency lead to a 3.3-fold increase in the risk of miscarriage in a sample group of 185 Caucasian women [32,33]. Literature also specifies that associations between MTHFR C667T mutations to factor V Leiden and prothrombin gene mutations were identified in patients having recurrent miscarriages [34].…”
Section: Miscarriagementioning
confidence: 97%
“…Both points of view bring scientific arguments and, against the fact that the controversy continues, it is generally accepted that homocysteine is involved in vascular endothelial dysfunction and promotes thrombosis [41][42][43]. The literature mentions many diseases in which elevated homocysteine concentrations have been found in the blood: cardiovascular diseases [36,[44][45][46][47][48], neurological diseases [49][50][51][52], miscarriage [53][54][55], thrombophilia [56][57][58][59][60][61], bone fragility [62][63][64][65][66][67], diabetes [68][69][70][71][72][73][74], inflammation [75][76][77].…”
Section: Homocysteine and Pregnancy Complicationmentioning
confidence: 99%
“…Clinical studies report that this mutation causes spontaneous abortions 3.3 times more frequently [53,54]. The particular case of the simultaneous mutation of MTHFR C667T, factor V Leiden, and/or prothrombin gene mutations will definitely cause recurrent pregnancy loss [55]. In addition to the thrombogenic effect, HHcy also manifests an effect of diminishing the fibrinolytic process.…”
Section: Homocysteine and Pregnancy Complicationmentioning
confidence: 99%